Innovative and new approaches to laboratory diagnosis of Zika and dengue: a meeting report - Goncalves, Adriana; Wilder-Smith, Annelies (The journal of infectious diseases, 2018)
Epidemics of dengue, Zika, and other arboviral diseases are increasing in frequency and severity. Current efforts to rapidly identify and manage these epidemics are limited by the short diagnostic window in acute infection, the extensive serologic cross-reactivity among flaviviruses, and the lack of point-of-care diagnostic tools to detect these viral species in primary care settings. The Partnership for Dengue Control organized a workshop to review the current landscape of Flavivirus diagnostic tools, identified current gaps, and developed strategies to accelerate the adoption of promising novel technologies into national programs. The rate-limiting step to bringing new diagnostic tools to the market is access to reference materials and well-characterized clinical samples to facilitate performance evaluation. We suggest the creation of an international laboratory-response consortium for flaviviruses with a decentralized biobank of well-characterized samples to facilitate assay validation. Access to proficiency panels are needed to ensure quality control, in additional to in-country capacity building.